Set up of a protocol for heparin use in special patients - N. Manresa Ramón; Mª D. Nájera Pérez; Mª Ángeles Page del Pozo; I. Sánchez Martínez; Mª del M. Sánchez Catalicio; V. Roldán Schilling (Farmacia Hospitalaria)
Low-molecular weight (LMW) heparins bring a series of advantages as compared to non-fractionated heparin (NFH), such as safety, efficacy, bioavailability, fewer monitoring, and persistent anti-coagulant response. There exist, however, a concern about their use in particular patients that may require a special control, such as those with renal failure, age over 75 years, obesity, and pregnancy. The aim of this study was the set up between the department of Pharmacy, Hematology, and Internal Medicine of a consensus protocol for the follow-up ad monitoring of LMWH in patients requiring a special control. For this purpose, we carried out a bibliographical review of the different heparins used under de above mentioned conditions. Based on the evidence available and the consensus among the members of the working group, we established a protocol that contained recommendations on prophylaxis, management and monitoring by means of the determination of anti-Xa factor. Besides, we included some clues on the therapeutic figures of anti-Xa and administration schedules for obtaining anti-Xa values within the range. Enoxaparin was the selected heparin given the evidence and its availability at our center.